Sistema remoto para análise automática de ECGs nos padrões HL7 AECG e DICOM-ECG - Lima, Marcelo Araújo (2017)
According to the World Health Organization, about 17.5 million people die each year from cardiovascular disease. The early diagnosis and treatment is crucial to reduce this high number of deaths from cardiovascular diseases. Due to the importance of the electrocardiogram (ECG) analysis, which represents one of the main tests for the detection of these cardiovascular diseases, in the present dissertation is proposed a remote system for automatic ECGs analysis based on webservices that can substantially assist the doctor, using the extracted ECGs information, with the purpose to generate reports. Hence, a Middleware is proposed to abstract the complexities and to facilitate the construction of tools that allow the ECGs automatic analysis. The proposed architecture consists on a server which provides the computational algorithms to identify the main waves present in ECGs such as QRS complex, P and T waves, and support the open standards of HL7 aECG and DICOM-ECG. In order to validate the proposed Middleware and contribute to the medical community, especially the Walter Cantídio University Hospital, a Web application for remotely accessible ECG report was developed. The proposed solution was tested using the database MITDB to simulate the patients of the system and produce the results presented in this dissertation. The proposed solution met the established requirements which makes the proposed solution viable financially and technically.